PELATIHAN TECHNOPREUNER UNTUK MENUMBUHKAN JIWA WIRAUSAHA - Prihantoro, C. Rudy; Avianti, Ratu Amilia; Jumhur, Aam Amaningsih (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract The solution offered to solve partner problems is Technopreneurship Training to Develop an Entrepreneurial Spirit in Teachers as educators. After the community service program is implemented, it is hoped that teachers can develop entrepreneurs. In the learning process, they must have networks and collaboration with the business/industry world. The implementation of Technopreneurship Training seeks to foster the entrepreneurial spirit of teachers. Presentation of entrepreneurship material includes: (1) the Technopreuner concept, developing a strong Technopreuner spirit - Business Management Managing a business with correct management starting from product design, to financial management. The training went very well and smoothly. All the training participants seemed very enthusiastic and listened seriously to the explanations from the speakers. Their appreciation for this training was not only because of the theory presented, but also because it was accompanied by direct practical sessions guided by resource persons. This makes complex materials easier to understand and implement. During the discussion and question and answer sessions, participants were very active in asking relevant questions regarding the material that had been presented. The resource person patiently and earnestly explained each question in detail and gave concrete examples. His response to each question demonstrated his expertise and proficiency in understanding and communicating the material effectively to the participants. Abstrak Solusi yang ditawarkan untuk menyelesaikan permasalahan mitra adalah Pelatihan Technopreneurship untuk Menumbuhkan Jiwa Technopreuner pada Guru sebagai pendidik. Setelah program pengabdian masyarakat dilaksanakan diharapkan Guru dapat mengembangkan entrepreneur dalam proses pembelajaran harus memiliki jaringan dan kerjasama dengan dunia usaha/industri.. Pelaksanaan Pelatihan Technopreneurship diusahakan menumbuhkan Jiwa wirausaha Guru. Penyampaian pemaparan materi kewirausahaan diantaranya: (1) konsep Technopreuner, mengembangkan semangat Technopreuner yang tangguh - Manajemen Usaha Mengelola usaha dengan manajemen yang benar mulai dari desain produk, hingga manajemen keuangan. Pelatihan berjalan dengan sangat baik dan lancar. Semua peserta pelatihan tampak sangat antusias dan menyimak penjelasan dari narasumber dengan sungguh-sungguh. Apresiasi mereka terhadap pelatihan ini bukan hanya karena teori yang disampaikan, tetapi juga karena disertai dengan sesi praktek langsung yang dibimbing oleh narasumber. Hal ini membuat materi yang kompleks menjadi lebih mudah dipahami dan diimplementasikan. Selama sesi diskusi dan tanya jawab, peserta sangat aktif dalam mengajukan pertanyaan-pertanyaan yang relevan seputar materi yang telah disampaikan. Narasumber dengan sabar dan penuh kesungguhan menjelaskan setiap pertanyaan dengan detail dan memberikan contoh yang konkret. Tanggapannya terhadap setiap pertanyaan menunjukkan keahlian dan kecakapannya dalam memahami dan mengkomunikasikan materi secara efektif kepada peserta.